Crystal collimation of heavy-ion beams at the Large Hadron Collider - S. Redaelli; O. Aberle; A. Abramov; R. Bruce; R. Cai; M. Calviani; M. D’Andrea; Q. Demassieux; K. Dewhurst; M. Di Castro; L. S. Esposito; S. Gilardoni; et al. (Physical Review Accelerators and Beams)
An important upgrade has been deployed for the collimation system of the Large Hadron Collider (LHC) for lead-ion beams that are already planned to reach their high-luminosity target intensity upgrade in the ongoing LHC Run 3 (2022–2026). While certain effects like e-cloud, beam-beam, impedance, injection, and dump protection are relaxed with ion beams, halo collimation becomes an increasing challenge, as the conventional multistage collimation system is about two orders of magnitude less efficient than that for proton beams. Ion fragments scattered out of the collimators in the betatron cleaning insertion risk quenching the cold dipole magnets downstream and may represent performance limitations. Planar channeling in bent crystals has been proven effective for high-energy heavy ions. A crystal collimation system was integrated into the LHC as a baseline solution for collimation in the High-Luminosity LHC (HL-LHC) era. In this paper, simulation and measurement results demonstrating the observation of channeling of heavy-ion beams and improvement in collimation cleaning in the multi-TeV energy regime are presented. The efficiency of the collimation scheme foreseen for the HL-LHC is presented. The highlights of the collimation performance in 2023, when crystal collimation was successfully deployed operationally for the first time, are also presented.